Molecular Tracking of the Leishmania Parasite - Moulik, Srija; Sengupta, Shilpa; Chatterjee, Mitali (Frontiers in Cellular and Infection Microbiology, 2021)
With the Visceral Leishmaniasis/Kala-azar Elimination Program in South Asia in its consolidation phase, the focus is mainly on case detection, vector control, and identifying potential sources of infection. Accordingly, emphasis is presently on curbing transmission, which is potentially achievable by identification and elimination of potential reservoirs. The strongest contenders for being the disease reservoir are cases of Post Kala-azar Dermal Leishmaniasis (PKDL) which occurs in a minor proportion of individuals apparently cured of Visceral Leishmaniasis (VL). The demonstration of parasites in tissue aspirates despite being a risky and invasive process is the gold standard for diagnosis of VL, but is now being replaced by serological tests e.g., rK39 strip test and direct agglutination test. However, these antibody based tests are limited in their ability to diagnose relapses, detect cases of PKDL, and monitor effectiveness of treatment. Accordingly, detection of antigen or nucleic acids by polymerase chain reaction has been successfully applied for monitoring of parasite kinetics. This review article provides updated information on recent developments regarding the available antibody or antigen/nucleic acid based biomarkers for longitudinal monitoring of patients with VL or PKDL and emphasizes the need for availability of studies pertaining to quantification of treatment response or relapse.